2007
DOI: 10.1111/j.1073-6077.2007.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating: Young Women's Search for Control and Connection

Abstract: Psychosocial and dietary assessments are necessary to identify youngsters without connected relationships and/or predispositions to disordered eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…This is supported by Nordbø et al . (2006), who described daily life structures, rules, and everyday planning as a way to achieve security, and by Budd (2007), who found that trying to gain control and connection was one basic process in young women's history of anomalous eating behaviour. Lies and hiding are also driven by shame.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Nordbø et al . (2006), who described daily life structures, rules, and everyday planning as a way to achieve security, and by Budd (2007), who found that trying to gain control and connection was one basic process in young women's history of anomalous eating behaviour. Lies and hiding are also driven by shame.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions were earlier considered Western phenomena, but as a consequence of a more global culture they are now seen all over the world in all social and cultural contexts 2. Eating disorders have been described as means of seeking control and consistency when life feels overwhelming 3,4. In an interview-based study, patients with anorexia nervosa described how their eating disorder gave them an inner feeling of drive, mastery, identity, and self-confidence, and how it helped them to obtain a sense of stability and security and to avoid negative emotions and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Another key finding of this study regards the mediating role of PWB in the relationships between the components of confirmation and body dissatisfaction as well as disordered eating behaviors. The associations between poor PWB—more specifically, low self‐esteem, depressive symptoms, and lack of satisfying social relationships—and body dissatisfaction as well as disordered eating have each been documented (e.g., Budd, ; Button, Sonugabarke, Davies, & Thompson, ; F. Johnson & Wardle, ). However, the mediating role of PWB on the links between family communication and issues surrounding body image and eating behaviors has thus far largely gone unexplored in communication research (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest that distressed feelings might transfer to the domain of the body and negatively color how young women feel about their bodies. Individuals with poor PWB might engage in disordered eating behaviors as a means of coping with issues they are dealing with, such as a sense of disconnection from others (e.g., Budd, ). Regardless of the reasons, results of the present study parallel previous research showing that psychological issues (e.g., depression, poor self‐esteem) prospectively predict body dissatisfaction and eating problems (e.g., Button et al, ; F. Johnson & Wardle, ).…”
Section: Discussionmentioning
confidence: 99%